2021
DOI: 10.1186/s12199-021-01004-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with food safety knowledge and practices among meat handlers in Bangladesh: a cross-sectional study

Abstract: Background Food handlers can play a vital role into reducing foodborne diseases by adopting appropriate food handling and sanitation practices in working plants. This study aimed to assess the factors associated with food safety knowledge and practices among meat handlers who work at butcher shops in Bangladesh. Methods A cross-sectional study was conducted among 300 meat handlers from January to March, 2021. Data were collected through in-person i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 26 publications
15
16
2
Order By: Relevance
“…In this study, all (52, 100%) meat handlers were males suggesting that meat retailing in Buea municipality is a male-dominated occupation. Our findings corroborate a very recent study by Al Banna et al [36] who reported that all 300 Bangladeshi meat handlers included in their study were males. Bafanda et al [37], in their study carried out in Jammu District of Jammu and Kashmir in India; Thakur et al [38], in another study in India; Junaidu et al [39], in Nigeria, all reported 100% male representation of the meat handlers.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, all (52, 100%) meat handlers were males suggesting that meat retailing in Buea municipality is a male-dominated occupation. Our findings corroborate a very recent study by Al Banna et al [36] who reported that all 300 Bangladeshi meat handlers included in their study were males. Bafanda et al [37], in their study carried out in Jammu District of Jammu and Kashmir in India; Thakur et al [38], in another study in India; Junaidu et al [39], in Nigeria, all reported 100% male representation of the meat handlers.…”
Section: Discussionsupporting
confidence: 93%
“…The multivariable logistic regression results showed that being a model household head (having received safety training) was a strong predictor of good food safety practices, which showed that the odds of performing good food safety practices among model household heads was 2.99 times higher compared to their counterparts. The result is corroborated by previous, similar studies, conducted in Debarq Town, 29 Gondar City, 7 Abobo district, 16 and Hawassa City, South Ethiopia, 25 Ghana, 33 Bangladesh, 34 Imo State, Nigeria, 27 and Saudi Arabia. 35 This could be explained by household heads who have received food safety training having a better understanding of safe food handling practices compared to household heads without food safety training.…”
Section: Discussionsupporting
confidence: 89%
“…The odds of performing good food safety practices among the study participants who had good knowledge of food safety practices was 2.05 times higher than in respondents who had poor knowledge. This study finding was also seen in previous studies carried out in Shashemene Town, Central Ethiopia, 26 Bole Sub-city, Addis Ababa, 18 Debre Markos Town, Ethiopia, 31 Dangila Town, 30 Gondar City, 7 and Debarq Town, Northwest Ethiopia, 29 Ghana, 1 Imo State, Nigeria, 27 Bangladesh, 34 Jordan, 37 and Sarawak and Petaling Jaya, Malaysia. 38 , 39 This association indicated that food safety practices are highly influenced by increasing knowledge scores regarding food safety.…”
Section: Discussionsupporting
confidence: 89%
“…In Bangladesh, few studies have been conducted to evaluate food safety knowledge, attitudes and practices of meat handlers, chicken vendors, fish farmers, food handlers of baking industries and consumers' knowledge and awareness of food safety [34][35][36][37][38]. While food safety in hospitals is a great matter of concern, there is a scarcity of published research on the knowledge, attitudes and practices of food service staff in Bangladeshi hospitals.…”
Section: Introductionmentioning
confidence: 99%